THE GEOLOGICAL LINKS OF THE ANCIENT DELPHIC ORACLE (GREECE): A REAPPRAISAL OF NATURAL GAS OCCURENCE AND ORIGIN - Etiope G.; Favali P.; Papatheodorou G.; Christodoulou D.; Geraga M. (My University, 2006)
Recent studies have speculated that the prophetic powers of Pythia, the woman of the Delphic Oracle, at the Temple of Apollo in Greece, were induced by hydrocarbon vapors, specifically ethylene, rising from bedrock fissures at the intersection of the E-W Delphi fault with the NNW-SSE Kerna fault, and producing neurotoxic effects, including trance and delirium. New surveys including gas flux from soil, gas in groundwater, and isotopic analyses of spring scales, provide the experimental confirmation of the gas release in the Delphi area. Presently, methane, ethane, and carbon dioxide are being released from a thermogenic (catagenetic) hydrocarbon-prone environment. This environment is not prone to biogenic production of ethylene in amounts inducing neurotoxic effects (hundreds or thousands of ppmv). A WNW-ESE-trending subsidiary fault within the Delphi fault zone, extending for ~2 km, passes under the Temple of Apollo and shrine of Athena. The Temple of Apollo, located above this fault, may have been the site of enhanced degassing in the past. If gas-linked neurotoxic effects upon Pythia need to be invoked, they should be sought in the possibility of oxygen depletion due to C02-CH4 exhalation in the indoor temple. Alternatively, a plausible geological explanation behind the natural presence of sweet scents could be the occurrence of aromatic hydrocarbons, such as benzene, dissolved in the groundwater spring. © 2006 Geological Society of America.
Keywords: DELPHI; ETHYLENE; FAULT; GAS; METHANE; SEEPS